Z = X + Y/X – 1/Y is an integer implies that
Z - X = (Y^2 - X)/(X*Y) is an integer, which then implies that
Z*X - X^2 = (Y^2 - X)/Y is an integer, which then implies that
Z*X - X^2 - Y = -X/Y is an integer.
Then this implies X is a multiple of Y; let X=K*Y.
Then back to the beginning:
Z = X + Y/X – 1/Y
Z = K*Y + Y/(K*Y) – 1/Y
Z = K*Y + 1/K - 1/Y
Now to satisfy the requirement for Z to be an integer, 1/K - 1/Y must be zero. (This is where the positive integer requirement speculated by broll comes into play, without that restriction then a nonzero 1/K-1/Y, like if Y=-2 and K=2, is possible.)
Then K=Y, which makes X=Y^2
Back to the beginning again:
Z = X + Y/X – 1/Y
Z = Y^2 + Y/(Y^2) - 1/Y
Z = Y^2 + 1/Y - 1/Y
Z = Y^2, a perfect square integer.
This verifies Jer's conjecture that X=Z=Y^2 forms the solution set (when the positive integer restriction is in place.)